Examination of the properties of Ti-6Al-4V based plates after oral and maxillofacial application - (:unkn) unknown (NATL INST OPTOELECTRONICS, 2007)
The objectives of this study were to investigate corrosion potential and alterations of mechanical features of Ti-6Al-4V plates after the short-term clinical use. The specimens were examined by imaging microscope, SEM and EDX, stereomicroscope, mechanical and chemical analysis methods. The results of the image analysis showed the presence of topographic alterations on the surfaces. Stereomicroscope examination demonstrated surface damages as surface cracks which occured during handling and application of the material. SEM and EDX results revealed that Ti-6Al-4V plates undergo local erosion due to biological interactions. A noticible decrease in microhardness, tensile strength, fatigue limit and failure values of removed plates was observed. Additionally, serum samples were chemically analysed and determined the concentrations of Ti, Al and V. In conclusion, the experimental results indicated that Ti-6Al-4V based plates had unsufficient corrosion resistance even after short-term clinical usage and they strongly emphasize that removed plates undergo corrosion and their mechanical properties weaken during their clinical function.
Keywords: Ti6Al4V plates; surface structure; mechanical and chemical analysis; corrosion; TITANIUM-ALLOYS; METALLIC BIOMATERIALS; RELEASE; REPLACEMENT; ALUMINUM